PENGEMBANGAN MODUL PEMBELAJARAN IPA BERBASIS KEARIFAN LOKAL DESA SEMBALUN UNTUK PENINGKATAN HASIL BELAJAR KOGNITIF SISWA MTs - Niza Fitriani; Ismail Efendi; Baiq Muli Harisanti (Bioscientist : Jurnal Ilmiah Biologi, 2019)
Local wisdom-based science learning modules are one of the science learning models that are oriented to the integration of the values of community local wisdom into science learning material. The aim of the study was to develop a science learning module based on the local wisdom of Sembalun Village to improve the cognitive learning outcomes of junior high school students. The research is a development research with a 4-D model design consisting of 4 stages: define, design, develop, and disseminate. Research instruments included local wisdom observation sheets, expert validation sheets, learning comprehension observation sheets, cognitive learning outcomes tests, and student response questionnaire sheets. Data collection techniques used is local wisdom observation techniques, validation, observation, tests, and questionnaires. The results of the study stated that the interview results obtained a total score of 62% with good categories. The modules that have been developed are then validated by 2 expert lecturers, with an average score of 3.70 with valid / non-revised categories. Implementation of learning (RPP) with an overall average score of 89.9% with a very good category. Cognitive learning outcomes of students in the small scale readability test with the N-Gain value of 0.36 with the medium category. Response of students with an overall average score of 3.47 in the good category. The results of the study can be concluded that the local wisdom based science learning module can improve the cognitive learning outcomes of VII class Mts Al-Banun students.